Central Line Associated Bloodstream Infections Outside the Intensive Care Unit: A 2-Year Analysis - Candevir, Aslıhan; Kurtaran, Behice; Kuşçu, Ferit; Kömür, Süheyla; Kibar, Filiz; Ertürk, Damla; İnal, Ayşe Seza; Taşova, Yeşim (Scientific Reports in Medicine, 2024)
Objective: There is limited data on the rates of central line-associated bloodstream infections (CLABSI) in non-intensive care units (ICU). Our aim was to determine the rates and features of CLABSI in non-ICU units.Method: CLABSI surveillance is performed according to CDC criteria in Internal Medicine Nephrology, Pediatric/Adult Hematology, Oncology and hematopoietic stem cell transplant (HSCT) units. Hospital infections control committee surveillance data was used.Results: Totally, 70028 patient days(pd) and 22358 catheter days, 101 infections were detected in 94 patients. The CLABSI rate was 1.44/1000 pd, the incidence density was 4.2/1000 catheter days, and the device utilization rate was 0.32. The highest infection rate was observed in the adult HSCT unit (15.18/1000 pd). 56.4% of the patients were male (n=53) and the mean age of the patients was 32±2.5 years. The mean length of hospitalization was 27.7±2.5 days. Half of the patients (n=47) had permanent central lines.  Hematologic cancer was found in 54.7% and hemodialysis in 19.2%. 21.8% of infections were polymicrobial. Of the 125 microorganisms isolated, 61.6% were Gram negative, 20.8% were fungi and 17.6% were Gram positive. The most frequent pathogen was E.coli (13.6%) followed by and K.pneumoniae (13.6%), Staphylococcus aureus (8%) and C.parapsilosis (7.2%). Crude mortality was 36.2%. Colistin and amikacin were the most effective antibiotics in E.coli and K.pneumoniae, oxacillin resistance was 60% in S. aureus. In Candida species, fluconazole resistance was 15.8%.Conclusion: CLABSI can also be seen outside intensive care units and surveillance in these units is necessary for infection control.
Keywords: Central venous catheter; Central line; Infection rate; Non-intensive care unit